UV-induced occupational skin cancer: possibilities of secondary individual prevention in the “dermatologist's procedure” - Elsner, Peter; Blome, Otto; Diepgen, Thomas L. (Journal der Deutschen Dermatologischen Gesellschaft, 2013)
Invasive squamous cell carcinoma (SCC) as a “quasi occupational disease” according to §9 Section 2 of the German Social Code Book (SGB) VII typically develops on chronically UV-damaged skin from actinic keratoses. After the Medical Scientific Committee of the Federal Ministry of Labor and Social Affairs has confirmed the legal criteria for acknowledging UV-induced SCC as an occupational disease, it is expected that the condition will be added to the official list of occupational diseases issued by the Federal Government in the near future. The Social Accident Insurance is required by law (§3 Occupational Disease Regulation) to prevent these tumors by “all appropriate means“. There are excellent therapeutic and preventive measures for the management of actinic keratoses to avoid the development of SCC. The “Dermatologist's Procedure“ according to §§ 41-43 of the agreement between the Social Accident Insurance and the Federal Medical Association was established in Germany in 1972 to take preventive measures in insured persons with skin lesions possibly developing into an occupational disease, or worsening it, or leading to a recurrence of it This procedure proved to be very successful in the prevention of severe and/or recurring skin diseases forcing a worker to leave his job. On the basis of this agreement, the Social Accident Insurance has the instruments to independently provide preventive measures for the new occupational skin disease SCC induced by natural UV light according to §9 Section 2 of the German Social Code Book (SGB) VII.
Gesehen am 05.02.2021